Strategi Pengembangan SDM Dan Operasional UMKM Warkop Hendri Jaya Kuphi Menggunakan Kerangka Mckinsey 7S - Siti Marwah (Indo Publishing, 2025)
This study aims to analyze human resource (HR) development strategies to improve operational performance at the Warkop Hendri Jaya Kuphi MSME through qualitative methods. The results show that the absence of SOPs, training, and clear task allocation results in slow service and inconsistent product quality. McKinsey 7S analysis reveals that the elements of strategy, structure, systems, staff, and skills are not aligned, thus hampering operational effectiveness. Strategies such as developing SOPs, training, digitalization, and reward systems are recommended to improve efficiency, service quality, and MSME competitiveness.